Integration of genome-wide association study and selection signatures reveals genetic determinants for skeletal muscle production traits in an F2 chicken population - Yu-dong LI; Xue BAI; Xin LIU; Wei-jia WANG; Zi-wei LI; Ning WANG; Fan XIAO; Hai-he GAO; Huai-shun GUO; Hui LI; Shou-zhi WANG (Journal of Integrative Agriculture, 2022)
Improving the production of broiler chicken meat has been a goal of broiler breeding programs worldwide for many years. However, the genetic architectures of skeletal muscle production traits in chickens have not yet been fully elucidated. In the present study, a total of 519 F2 birds, derived from a cross of Arbor Acres broiler and Baier layer, were re-sequenced (26 F0 individuals were re-sequenced at a 10-fold depth; 519 F2 individuals were re-sequenced at a 3-fold depth) and the coupling of genome-wide association study (GWAS) and selection signatures (FST (fixation index) and θπ (nucleotide diversity)) was carried out to pinpoint the associated loci and genes that contribute to pectoral muscle weight (PMW) and thigh muscle weight (TMW). A total of 7 890 258 single nucleotide polymorphisms (SNPs) remained to be analyzed after quality control and imputation. The integration of GWAS and selection signature analyses revealed that genetic determinants responsible for skeletal muscle production traits were mainly localized on chromosomes 1 (168.95–172.43 Mb) and 4 (74.37–75.23 Mb). A total of 17 positional candidate genes (PCGs) (LRCH1, CDADC1, CAB39L, LOC112531568, LOC112531569, FAM124A, FOXO1, NBEA, GPALPP1, RUBCNL, ARL11, KPNA3, LHFP, GBA3, LOC112532426, KCNIP4, and SLIT2) were identified in these regions. In particular, KPNA3 and FOXO1 were the most promising candidates for meat production in chickens. These findings will help enhance our understanding of the genetic architecture of chicken muscle production traits, and the significant SNPs identified could be promising candidates for integration into practical breeding programs such as genome-wide selection (GS) to improve the meat yield of chickens.